Implikasi Putusan Mahkamah Konstitusi Nomor 92/PUU-XIV/2016 terhadap Independensi Komisi Pemilihan Umum - Allan Fatchan Gani Wardhana (Fakultas Hukum Universitas Jambi, 2018)
The General Elections Commission (KPU) is an independent state institution directly regulated in Article 22E of the 1945 Constitution of the Republic of Indonesia. Its position as an independent state institution affirms that the KPU is not under the influence of the DPR and the government in carrying out its duties and authorities. Article 9 Sub-Article a of Law Number 10 Year 2016 (Regional Head Election Law) stipulates the requirement of the KPU to consult the DPR and the Government in drafting and enacting KPU regulations and technical guidelines for each election stage in forums of hearings whose decisions are binding. The Constitutional Court through Decision Number 92/PUU-XIV/2016 finally canceled the word